ANALISIS KECUKUPAN PRASARANA PENDIDIKAN FAKULTASTEKNIK UNY UNTUK MENDUKUNG PROGRAM RENSTRATAHUN 2010-2014 - Sumarjo H, dan Didik Purwantoro (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2012)
This research aim to (1) perform of educational infrastructure; (2) predictiveindex calculation and efficiency of educational infrastructures; (3) Necessity,sufficiency and lack of educational infrastructure to support developmentprogramme. The research method is quantitative descriptive The research method isquantitative descriptive. primary data research from academic, administrativedocuments, building infrastructure, and renstra. secondary data is a standardregulatory space, and the situation of the Department. The technique of datacollection is by the study of documents, field observations, and interviews with theleaders of departments and units. The results showed that the average of theoriesclass space of Engineering Faculty is 73,13%, workshop and Laboratory room, lessthan 100%. The level of sufficiency of lecturer and head of deparment was the resultless than 50%. Whenever was calculated with space of lecturer on Laboratory ofLPTK, the result is 79.18%. in the future, The development of the space of a lectureron each other.Keyword: Educational, infrastructure